Cellular functions and molecular mechanisms of non-lysine ubiquitination. Issue 9 (18th September 2019) - McClellan, Amie J.; Laugesen, Sophie Heiden; Ellgaard, Lars
Abstract : Abstract : Protein ubiquitination is of great cellular importance through its central role in processes such as degradation, DNA repair, endocytosis and inflammation. Canonical ubiquitination takes place on lysine residues, but in the past 15 years non-lysine ubiquitination on serine, threonine and cysteine has been firmly established. With the emerging importance of non-lysine ubiquitination, it is crucial to identify the responsible molecular machinery and understand the mechanistic basis for non-lysine ubiquitination. Here, we first provide an overview of the literature that has documented non-lysine ubiquitination. Informed by these examples, we then discuss the molecular mechanisms and cellular implications of non-lysine ubiquitination, and conclude by outlining open questions and future perspectives in the field.